Weight - based victimization : associations with body objectification and emotional reactions in adolescents - Ho, Thu Ha (Đại học Quốc gia Hà Nội, 2020)
In the past decades, a large body of research suggested that body weight is one of the most common reason for school bullying ( Puhl, Luedicke, & Heuer, 2011 ), and weight - based victimization (e.g. teasing and bullying) is associated with various physical and mental health negative consequences (Puhl & Luedicke, 2012 ). Recent studies in Vietnam have shown a growing interest in the field of bullying, but there's still a lack of attention for weight - based victimization (WBV). Given the need for understanding about the situation of WBV in Vietnam, this study aims to examine the prevalence of WBV in adolescents, its emotional impact and its link with objectified body consciousness (an unhealthy process in adolescent, defined as the tendency to view themselves as objects to be evaluated). Methods : Self - report data was collected from a sample of 365 high school students in Hanoi on their experiences of WBV, their emotional responses, and their objectified body consciousness (OBC). Thirty - seven point three percent of participants reported being victimized at school. The reported forms of victimization include verbal, physical, relational and cyberbullying. More than 40 % of participants experienced negative affects about themselves after being bullied or teased by their weight. WBV was positively correlated with objectified body consciousness in general (r=0.20: p<0.01) and body shame in particular (r=0.21; p<0.01). Among four types of WBV, verbal bullying is positively correlated to body shame and control belief (r=0.24 0.25; p<0.01). Moreover, negative affect in response to WBV was strongly related to all components of OBC (r=0.38-0.55; p<0.01). Results indicated a high prevalence of WBV and its association with objectified body consciousness among adolescents , highlighting the need of WBV prevention programs which should include body image improvement as a target